The impact of threat of shock on the framing effect and temporal discounting: executive functions unperturbed by acute stress? - Robinson, Oliver J.; Bond, Rebecca L.; Roiser, Jonathan P. (Frontiers in Psychology, 2015)
Anxiety and stress-related disorders constitute a large global health burden, but are still poorly understood. Prior work has demonstrated clear impacts of stress upon basic cognitive function: biasing attention towards unexpected and potentially threatening information and instantiating a negative affective bias. However, the impact that these changes have on higher-order, executive, decision-making processes is unclear. In this study we examined the impact of a translational within-subjects stress induction (threat of unpredictable shock) on two well-established executive decision-making biases: the framing effect (N=83), and temporal discounting (N=36). In both studies, we demonstrate a) clear subjective effects of stress, and b) clear executive decision-making biases but c) no impact of stress on these decision-making biases. Indeed, Bayes factor analyses confirmed substantial preference for decision-making models that did not include stress. We posit that while stress may induce subjective mood change and alter low-level perceptual and action processes (Robinson et al., 2013b), some higher-level executive processes remain unperturbed by these impacts. As such, although stress can induce a transient affective biases and altered mood, these need not result in poor financial decision-making.